1990
DOI: 10.1105/tpc.2.9.941
|View full text |Cite
|
Sign up to set email alerts
|

Two Closely Related Wheat Storage Proteins Follow a Markedly Different Subcellular Route in Xenopus laevis Oocytes.

Abstract: [alpha]-Gliadins and [gamma]-gliadins are two closely related wheat storage proteins that evolved from a common ancestral gene. However, synthesis of [alpha]-gliadins and [gamma]-gliadins in Xenopus laevis oocytes revealed striking differences in their subcellular routing. The major portion of [alpha]-gliadin accumulated inside the oocyte, whereas most of the [gamma]-gliadin was secreted. Disruption of the Golgi apparatus by monensin revealed that the major part of secretion of [gamma]-gliadin is Golgi mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Moreover, a maize a-zein that was expressed in yeast accumulated within the ER of these cells (Coraggio et al, 1988). Accumulation of the 7-gliadin within the ER of the yeast cells was much more effective than that of a similar 7-gliadin expressed in Xenopus oocytes, where 50 to 80% of the protein was secreted via the Golgi to the medium (Simon et al, 1990;Altschuler et al, 1993). One possible explanation for this is that the 7-gliadin was not folded correctly within the ER of the yeast.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, a maize a-zein that was expressed in yeast accumulated within the ER of these cells (Coraggio et al, 1988). Accumulation of the 7-gliadin within the ER of the yeast cells was much more effective than that of a similar 7-gliadin expressed in Xenopus oocytes, where 50 to 80% of the protein was secreted via the Golgi to the medium (Simon et al, 1990;Altschuler et al, 1993). One possible explanation for this is that the 7-gliadin was not folded correctly within the ER of the yeast.…”
Section: Discussionmentioning
confidence: 96%
“…This supports our suggestion that retention of the 7-gliadin within the ER was not related to the phenomenon of oligomer formation during extraction. Thus, it seems likely that the efficient retention of the 7-gliadin within the ER of the yeast cells was related to the process of PB formation or to specific interactions of this protein with ER-resident proteins, such as BiP or other Ca 2+ -binding reticuloplasmins (Both and Koch, 1989;Sambrook, 1990;Simon et al, 1990;Suzuki et al, 1991). Such processes are apparently dictated by the N-terminal region of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments by Ceriotti et al (1992) show that trimerization of the phaseolin subunits (a storage protein in bean seeds) is required for the transport of the protein out of the ER in Xenopus oocytes. By expressing a-and ]3-gliadins in Xenopus oocytes, Simon et al (1990) indicated the presence of two different routes for the transport of these wheat storage proteins from the ER to the vacuoles.…”
Section: Introductionmentioning
confidence: 98%
“…In wheat seed, storage proteins are deposited in two different types of PBs inside vacuoles (Rubin et al, 1992). Two separate routes to the vacuole have been postulated with regard to the transport of gliadins and glutelins: one is via the Golgi complex and the other is by way of an autophagy-like pathway (Simon et al, 1990;Levanony et al, 1992). Noncovalent interaction and disulfide bond cross-links between glutelins and/or gliadins seem to direct PB formation in the wheat endosperm (Shani et al, 1992).…”
Section: Introductionmentioning
confidence: 99%